The Central Roles of Noncoding RNA in Estrogen-Dependent Female Reproductive System Tumors - Jiajie Tu; Huan Yang; Lei Jiang; Yu Chen; Yu Chen; Zhe Li; Lei Li; Yuanyuan Zhang; Xiaochun Chen; He Chen; Zhiying Yu (International Journal of Endocrinology)
The pathogenesis of ovarian and endometrial cancers is closely associated with estrogen-related pathways. These estrogen-dependent tumors seriously threaten the health and quality of life in women. Noncoding RNAs (ncRNAs) are defined as RNAs that do not encode proteins, including microRNAs (miRNAs) and long noncoding RNAs (lncRNAs), both of which have been reported in estrogen-dependent female reproductive system tumors. This review systematically summarizes the role of ncRNAs in estrogen-dependent tumors and common patterns of regulatory mechanisms to explore their future research directions in tumor diagnosis, treatment, and prognosis. This may provide new ideas for the potential application of ncRNAs in estrogen-dependent female reproductive system tumors.